From Aristotle to happiness in public policy in Peru. Reflections from a study across two strata - Ibáñez, Franklin (2020)
Over the last decades, happiness has become an important subject addressed by several disciplines, leading  to reflection on its possible application in public policies.  An interdisciplinary team of researchers has brought together the most common notions associated with happiness in Peru, based on interviews with heads of households in the poorest and the wealthiest districts in the  country. This paper will examine those findings from the  Aristotelian theoretical framework, in order to provide a  theoretical basis for possible public policies. The classical  Aristotelian or Eudaimonism theory distinguishes between  superficial and more profound conceptions of happiness.  This article asserts that policies oriented to happiness foster full lives that include access to health, education and  employment, and the encouragement of citizen solidarity, while demythologizing the idea that poor people only  need or want money in order to be happy.